2014
DOI: 10.1016/j.freeradbiomed.2014.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Metal chelator combined with permeability enhancer ameliorates oxidative stress-associated neurodegeneration in rat eyes with elevated intraocular pressure

Abstract: Since as many as half of glaucoma patients on intraocular pressure (IOP)-lowering therapy continue to experience optic nerve toxicity, it is imperative to find other effective therapies. Iron and calcium ions play key roles in oxidative stress, a hallmark of glaucoma. Therefore, we tested metal chelation by means of ethylenediaminetetraacetic acid (EDTA) combined with the permeability enhancer methyl sulfonyl methane (MSM) applied topically on the eye to determine if this non-invasive treatment is neuroprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…Among the various signaling targets of HNE, are cell cycle regulators such as,c-Jun NH2-terminal kinase (JNK), p38 mitogen-activated protein kinases (p38MAPK), , protein kinase C-β and -δ (PKC-β and PKC-δ) [49]. Oxidative stress/HNE can inactivate and down regulate ALDH and induce toxicity; conversely activation and upregulation of ALDH prevents oxidation-/HNE-associated damage in cells and tissues [1819,2123,25,26,52–55] Our current study, for the first time, demonstrates that thermal injury induced a long lasting decrease in the expression of two of ALDH1A1 and ALDH2 in the untreated unburned interspaces. The decreased expression of these enzymes may be a result of direct effect of heat energy itself or other inflammatory factors released after thermal injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various signaling targets of HNE, are cell cycle regulators such as,c-Jun NH2-terminal kinase (JNK), p38 mitogen-activated protein kinases (p38MAPK), , protein kinase C-β and -δ (PKC-β and PKC-δ) [49]. Oxidative stress/HNE can inactivate and down regulate ALDH and induce toxicity; conversely activation and upregulation of ALDH prevents oxidation-/HNE-associated damage in cells and tissues [1819,2123,25,26,52–55] Our current study, for the first time, demonstrates that thermal injury induced a long lasting decrease in the expression of two of ALDH1A1 and ALDH2 in the untreated unburned interspaces. The decreased expression of these enzymes may be a result of direct effect of heat energy itself or other inflammatory factors released after thermal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms by which the metals initiate LA production is not entirely understood [16], trace metals such as iron and copper are recognized as effective catalysts in the initiation of LA production [17,]. In addition, our previous studies have demonstrated that the topical application of metal chelators such as EDTA (ethylenediaminetetraacetic acid) ameliorated oxidative and inflammatory markers in rat models of glaucoma [18] and diabetic cataract [19]. …”
Section: Introductionmentioning
confidence: 99%
“…For instance, topical EDTA-MSM is effective at reducing oxidative damage in the form of protein-lipid aldehyde adducts [170,171,172]. EDTA-MSM reduced lens opacification in diabetic cataract [172] but was ineffective in reversing experimentally induced intraocular pressure in rats [170]. In humans, EDTA-MSM lotion significantly improved pitting edema symptoms after two weeks of application, with circulating total antioxidant capacity and MDA reductions noted [173].…”
Section: Common Usesmentioning
confidence: 99%
“…A number of hypotheses have been proposed regarding the pathogenesis of glaucoma, however there is currently no hypothesis that fully explains the pathological changes occurring. Although the mechanisms underlying glaucoma are not well understood, it has been established that glaucoma does not result from a single pathological mechanism, but rather a combination of pathways influenced by genes, age and environment (10)(11)(12)(13)(14)(15)(16)(17)(18). Despite this, there remain many unsolved problems, such as the effect of nuclear transcription factor regulation in glaucoma, that warrant further study (19).…”
Section: Introductionmentioning
confidence: 99%